Factibilidad para la Implementación de una Empresa Productora y Comercializadora de Pasteles con endulzantes Stevia, para personas diabéticas en la Ciudad de Loja - Illescas Burguan, Mónica Alexandra (2017)
The present work of thesis is about the study of "FEASIBILITY FOR THE IMPLEMENTATION OF A PRODUCTION AND MARKETING COMPANY OF PASTRIES WITH STEVIA ENDULZANTS FOR DIABETIC PERSONS IN THE CITY OF SHOP", has the purpose to contribute to the business development of the city, Economics for a Better standard of living for its inhabitants. In the research process, the aspects, concerns to the theoretical basis and the practical context of the project stand out, for which an effect is applied the application of several investigative techniques and methods, which resulted in the obtaining of information, Which should have been interpreted and analyzed using the methods before arriving. Within the investigation was made a brief diagnosis and market study regarding the potential demand was determined to determine an amount of 276,680 cakes that consume a year. Regarding the technical study, in relation to the installed capacity, an estimated 70,080 cakes per year, while for the used capacity of previous amount of 16,640 cakes per year. Likewise, the legal and administrative organization was elaborated, where it was established that the company worked under the name of "Limited Liability Company", establishing its Corporate Name as "PASTELERIA DIASTEVIA Cía. Ltda.", during 5 years of useful life . 5 For the execution of this project there is an investment of $ 35,556.29. The main objective of this work was to determine the feasibility of the investment project for its subsequent implementation with a 5-year horizon in the city of Loja, and this is how the financial evaluation indicators projected positive results The Internal Rate of Return (IRR) corresponds to 70.14%, while the Capital Recovery Period (PRC) is 0.22 ctv. For every dollar of investment. As regards the Cost Benefit Ratio (RBC), it is established that the capital investment was recovered in the first year of the company's operation, with 4 months and 13 days. Finally the sensitivity analysis shows that for the increase in costs the project allows an increase rate of 12.16% and for the decrease of income, the rate of rotation corresponds to 9.99% of the percentage of decrease. After having realized the studies was determined that the project is feasible